Cost-effectiveness of nicotine patches for smoking cessation in pregnancy: a placebo randomised controlled trial (SNAP) - Essex, Holly; Parrott, Steve; Wu, Qi; Li, Jinshuo; Cooper, Sue; Coleman, Tim (Oxford University Press, 2014)
Introduction: Smoking during pregnancy is the most important, preventable cause of adverse pregnancy outcomes including miscarriage, premature birth and low birth weight, with huge financial costs to the NHS. However, there are very few published economic evaluations of smoking cessation interventions in pregnancy and previous studies are predominantly US-based and do not present incremental cost-effectiveness ratios (ICER). A number of studies have demonstrated cost-effectiveness of nicotine replacement therapy (NRT) in the general population, but this has yet to be tested among pregnant smokers.